Subtract x² –
3x + 2 from the sum of 2x - 4x² + 9 and 3x + 5x² _4x^2
Answers
Answered by
0
Step-by-step explanation:
(x^2-3x+2) - ( (2x-4x^2+9) + (3x+5x^2-4x^2) )
= (x^2-3x+2) - (5x-4x^2+9+x^2)
=(x^2-3x+2) - (5x-3x^2+9)
=x^2-3x+2-5x+3x^2-9
=4x^2-8x-7
Answered by
0
Answer:
answer for the given problem is given
Attachments:
![](https://hi-static.z-dn.net/files/d15/1db18693badad52d6fa3e896b86ec3b8.jpg)
Similar questions
Science,
3 months ago
Art,
3 months ago
Math,
7 months ago
Psychology,
7 months ago
Computer Science,
1 year ago